Three types of kinetics and instability for enzymatic glucose fuel cell models - Kawinwit, Kuntida; Koonprasert, Sanoe; Charoenloedmongkhon, Akapak (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Mathematical modeling plays an important role in biochemistry having various enzymatic fuel cell problems. Enzymes are the basis of life activities and involved in almost all chemical reactions in organisms. The metabolic system of many anabolic and catabolic reactions under the catalysis of enzymes, which the study of the chemical reactions that are catalyzed by enzymes is called enzyme kinetics. This paper aims to discuss the enzyme kinetics term of the enzymatic glucose fuel cells. We apply three types of enzyme kinetics including the Michaelis Menten equation, the Morrison equation (Quadratic Velocity Equation) and the multiple substrate binding sites into the models. We analyze the equilibrium points, local stability of the models and plot some graphs of the glucose and hydrogen ion concentrations with time across the enzymatic glucose fuel cells by the Maple program.